2017
DOI: 10.1111/1759-7714.12454
|View full text |Cite
|
Sign up to set email alerts
|

Elevated pretreatment neutrophil/white blood cell ratio and monocyte/lymphocyte ratio predict poor survival in patients with curatively resected non‐small cell lung cancer: Results from a large cohort

Abstract: BackgroundThe prognostic values of preoperative neutrophil/lymphocyte ratio (NLR), monocyte/lymphocyte ratio (MLR), and platelet/lymphocyte ratio (PLR) in non‐small cell lung cancer (NSCLC) have been previously described. This study assessed the prognostic values of other pretreatment complete blood cell parameters in Chinese patients with curatively resected NSCLC.MethodsA total of 1466 consecutive NSCLC patients who received curative surgery from January 1, 2005 to December 31, 2009 with complete data from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 29 publications
(35 reference statements)
1
58
0
Order By: Relevance
“…Accumulated evidence suggests that inflammation plays an essential role in tumorigenesis and tumor progression, which is now included as a hallmark of cancer . The peripheral inflammatory cells and calculated ratios, especially neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR), have been demonstrated as independent prognostic biomarkers in various cancers, including breast cancer, esophageal carcinoma, colorectal carcinoma, and lung cancer . Opposing to the TNM staging system, which only represents the status of tumor, NLR and PLR could reflect the inflammatory status of host and supplement the TNM staging system.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence suggests that inflammation plays an essential role in tumorigenesis and tumor progression, which is now included as a hallmark of cancer . The peripheral inflammatory cells and calculated ratios, especially neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR), have been demonstrated as independent prognostic biomarkers in various cancers, including breast cancer, esophageal carcinoma, colorectal carcinoma, and lung cancer . Opposing to the TNM staging system, which only represents the status of tumor, NLR and PLR could reflect the inflammatory status of host and supplement the TNM staging system.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evaluated the role of absolute leucocyte, neutrophil, monocyte, lymphocyte or platelet count, ratios of various parameters like neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio among others and found conflicting results and a variety of threshold values with prognostic importance [9], [10], [11], [12], [13], [14]. However, most of these studies have evaluated patients with advanced stage or medically operable early stage NSCLC who underwent surgery.…”
Section: Introductionmentioning
confidence: 99%
“…37 Studies regarding the monocyte count in peripheral blood have been performed in the field of cancer survival. 18,19,38 These studies reported that an elevated monocyte count has a worse effect on patients' survival. This finding suggests that an elevated monocyte count has an immunosuppressive effect.…”
Section: Philscanactasantigen-presentingcellsandactivateprimarycd4+mentioning
confidence: 99%
“…The monocyte count is one of the key players in transplant immunology; however, reports about the relationship between the peripheral monocyte count and rejection are scarce . It is well known that a high monocyte count in peripheral blood has a deleterious effect on survival in patients with cancer …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation